University-Industry Collaboration and Innovation Performance: Evidence from the University of Surabaya in Indonesia - Lianto, Benny; Iswadi, Hazrul; Oktaviyanti, Nina Dewi (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. The Indonesian government, through the Ministry of Education, Culture, Research, and Technology (Kemdikbudristek) has introduced the Matching Fund (MF) program. MF is a concrete form of government support and intervention to create collaboration and strategic synergy between higher education institutions (universities) and industry. This study aims to investigate and analyze various forms of collaboration and interaction between universities and industry and their impact on innovation performance in the Matching Fund (MF) program. This study uses an interpretive qualitative methodology with eight (8) case studies of the MF program at the University of Surabaya, Indonesia, during the period 2021 to 2023. The results of the study show that the forms of interaction that occur are very diverse, ranging from informal to very formal interactions. This study also shows that the number and form of interactions are not influenced by the duration of the collaboration. The variety of forms of interaction is more determined by the quality of the company and university leaders, good relationships and mutual trust between the two parties, good relationships, coordination, and communication between the persons in charge (PICs) of the two parties. Furthermore, the results of the study show that the MF program provides direct innovation outcome (DIO) and indirect innovation outcome (IIO) results for companies. On the other hand, the MF university-industry collaboration program also provides positive results for the universities in terms of DIO and IIO, but not all university-industry collaboration projects provide maximum results for academic innovation (AI). The duration of cooperation, mutual trust, and good coordination and communication between the persons in charge (PICs) of the two parties all have a greater influence on AI. Keywords: University, Industry, Collaboration, Matching Fund, and Innovation Performance